0

# What facts are missing from the problem? 12 + 5x = 6 - x

12 + 5x = 6 - x

### 2 Answers by Expert Tutors

Kyle M. | Certified Educator with Masters, Tutoring 3rd Grade Through CollegeCertified Educator with Masters, Tutorin...
4.9 4.9 (164 lesson ratings) (164)
0
This problem can be solved with the given information, so we should find that no facts are missing:
12 + 5x = 6 - x
12 + 5x + x = 6 - x + x
Combine like terms:
12 + 6x = 6
Subtract 12 from each side:
12 - 12 + 6x = 6 - 12
Do the arithmetic:
6x = -6
Divide each side by 6:
x = -1
Jessica B. | Knowledgeable in Almost Everything from Elementary Through College!Knowledgeable in Almost Everything from ...
5.0 5.0 (4 lesson ratings) (4)
0
To solve this equation the first step is to get X on one side of the =.

12+5x=6-x

To get x to one side, you need to add x to both sides.  This will cancel out x from the right side of the equation and on the left it will become 6x.

12+6x=6

Now you simply need to solve for x.  To do this you simply need to reverse the order of operations.
The first step to doing this is to subtract 12 from both sides.  This cancels out 12 on the left.

6x= -6

Now divide both sides by 6.  On the left the 6 is cancelled out in this step so you are left with x.  The right side is the solution.

x= -1